2012
DOI: 10.1002/mnfr.201200206
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of starch digestion by the green tea polyphenol, (−)‐epigallocatechin‐3‐gallate

Abstract: Scope Green tea has been shown to ameliorate symptoms of metabolic syndrome in vivo. The effects could be due, in part, to modulation of postprandial blood glucose levels. Methods and results We examined the effect of coadministration of (−)-epigallocatechin-3-gallate (EGCG, 100 mg/kg, i.g.) on blood glucose levels following oral administration of common corn starch (CCS), maltose, sucrose, or glucose to fasted CF-1 mice. We found that cotreatment with EGCG significantly reduced postprandial blood glucose le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(122 citation statements)
references
References 39 publications
7
114
1
Order By: Relevance
“…Although there have been few studies on the effects of dietary supplementation with propolis on enzyme activity, decreased amylase activity may be related to the complex composition of polyphenols in propolis. Several authors have reported that amylase activity may be reduced by anthocyanins, phenolic acids and flavonoids in the diet (McDougall et al 2005;Tadera et al 2006;Forester et al 2012). In fact, Matsui et al (2004) also showed an inhibitory effect of propolis on amylase activity and as suggested by Hashim et al (2013), the nature of amylase inhibition by polyphenols is non-competitive.…”
Section: Resultsmentioning
confidence: 97%
“…Although there have been few studies on the effects of dietary supplementation with propolis on enzyme activity, decreased amylase activity may be related to the complex composition of polyphenols in propolis. Several authors have reported that amylase activity may be reduced by anthocyanins, phenolic acids and flavonoids in the diet (McDougall et al 2005;Tadera et al 2006;Forester et al 2012). In fact, Matsui et al (2004) also showed an inhibitory effect of propolis on amylase activity and as suggested by Hashim et al (2013), the nature of amylase inhibition by polyphenols is non-competitive.…”
Section: Resultsmentioning
confidence: 97%
“…This result was comparable to the inclusion of crude propolis , which showed that pancreatic amylase activity decreased with dietary inclusion of crude propolis, possibly related to the inhibitory effect of propolis polyphenols on amylase and maltase activity (MATSUI et al, 2004;ZHANG et al, 2015), despite the low concentration of these compounds in the residue. Many authors have shown that amylase and maltase activity may be decreased by anthocyanins, phenolic acids, and flavonoids (FORESTER et al, 2012;HANHINEVA et al, 2010;MCDOUGALL et al, 2005). This is due to either non-competitive inhibition associated with the number of hydroxyl groups on the B-ring of the flavonoid skeleton, and consequent formation of hydrogen bonds between the hydroxyl groups of the polyphenol ligands and catalytic site of the enzyme (LO PIPARO et al, 2008), or the antioxidant properties of the polyphenols, which may also inhibit amylase activity (HASHIM et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Matsui et al (2004) reported that the bioactive constituents of propolis can inhibit α-glucosidase activity [38]. Similarly, epigallocatechin gallate (EGCG), the primary flavonol in green tea, has been shown to inhibit -amylase activity [39] and both grape seed and tea extracts were potent inhibitors of both -amylase and -glucosidase activity in healthy volunteers [40]. In a meta-analysis of 17 randomized controlled trials it has been reported that the beneficial effect of natural antioxidants upon glycemia may be more pronounced in subjects that are at higher risk for metabolic syndrome [41].…”
Section: Discussionmentioning
confidence: 99%